2020
DOI: 10.1080/19477503.2020.1827663
|View full text |Cite
|
Sign up to set email alerts
|

The Qualms and Quarrels with Online Undergraduate Mathematics: The Experiences of African American Male STEM Majors

Abstract: Equity-related issues are a critical contemporary concern in mathematics education, and one specific area that has been taken up deals with equitable instructional modalities. However, the focus of many of these discussions, meetings, and publications is on K-12 mathematics education. This study reports on one aspect of an ongoing, equity issue in undergraduate mathematics educationface-to-face versus online mathematics instruction. In so doing, it investigates this issue surrounding online mathematics learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Finally, disturbances in the flow of classes can impede students' willingness to accept online distance learning (Nambiar, 2020). Jett (2020) pointed out that there are more distractions when students are learning online at home. All in all, these factors are tied together to the previous literature of Technology Acceptance Model (Davis, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, disturbances in the flow of classes can impede students' willingness to accept online distance learning (Nambiar, 2020). Jett (2020) pointed out that there are more distractions when students are learning online at home. All in all, these factors are tied together to the previous literature of Technology Acceptance Model (Davis, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…(Guerrero et al, 2020). Even high achieving African American, male STEM students found that the nature of their online math course was pedagogically ineffective (Jett, 2021). Palacios and Wood (2016) found that the asynchronous, multi-media modality was effective for Black men but warned that in general, careful consideration be used when promoting online learning to Asian, Black, Latino, and white men at community colleges because of their overall preference for face-to-face modalities.…”
Section: Course Designmentioning
confidence: 99%